Is There a Future for Capital Income Taxation? - Mintz, Jack M.. (OECD Publishing, 1992)
This paper examines the future of capital income taxation in a world of capital mobility. It first explores the motivation for personal and corporate income taxation in an open economy and argues that policymakers should view these taxes as having quite different impacts on the economy. The paper then suggests that some forces (e.g. capital flight) will encourage governments to shift away from capital income taxation while others (e.g. tax exportation) will have the opposite effect ...
Keywords: Economics